Thought Presentation in Alice Sebold’s The Lovely Bones - Shahid Ahmad; Shanthi Nadarajan (Journal of Language and Literature, 2020)
The last three decades have witnessed an increasing interest in the studies of thought presentation in stream-of-consciousness narratives among linguists (Semino Short, 2004; Leech Short, 2007; Bray, 2014; Fludernik, 1993). Largely because fictional writers use thought presentation in various ways to get readers to understand direct and indirect thoughts of the characters. Feminist writers have employed thought presentations in stream-of-consciousness narratives to give voice to the sufferings and yearnings of women and children. It has been done through careful selection of language that includes lexical choices, grammatical categories, and meaning representation. Besides providing multiple perspectives to the character’s experiences through definition, reasoning, and arguments, the use of differentiated meanings and metaphorical language in thought presentations has served as insights into the minds of killers and criminals. This paper uses stylistic analysis to explore the conscious and sub-conscious thought presentations of Susie Salmon, the protagonist, and Mr. Harvey, the antagonist in Alice Sebold’s The Lovely Bones (2002). For the study, the researchers use Geoffrey Leech and Michael Short’s (2007) model of thought presentation.The analysis will delve into the thought patterns of ‘dead’ Susie when she meets her assailant. It investigates lexical selection, semantics, and linguistic patterns. The findings show that thought patterns residing even in the sub-conscious or unconscious of human beings can be reached by analyzing thought representations embedded in a narrative discourse through a variety of thought presentation techniques. The central assumption being that while it takes courage to write about death and rape, it takes imagination to a new realm when a ‘dead’ girl returns to talk about her rape and death.